Sea level rise inducing tidal modulation along the coasts of Bengal delta. (30th December 2020) - Khan, Md Jamal Uddin; Durand, Fabien; Testut, Laurent; Krien, Yann; Islam, A.K.M. Saiful
Abstract: The Bengal delta, the largest delta on the Earth, is subject to a marked coastal flooding hazard and associated with widespread vulnerability. The situation will expectedly deteriorate in the ongoing context of sea level rise. This sea level rise will not only have a direct effect on the coastal flooding, but will also have indirect effects, through the alteration of the coastal hydrodynamics. In the present study, we investigate the impact of sea level rise on tide, which is the largest source of variability of sea level along the macro-tidal coast of Bengal delta. Through a comprehensive modelling framework comprising the coastal delta, major estuaries, as well as the intricate hydraulic network of the delta, we assess the future changes of tidal properties to be expected for various sea level rise scenarios, representative of the end of the 21st century and beyond. It is found that the effect is large, and regionally dependent. Over both the south-western and south-eastern parts of the delta, the amplitude of the tide is expected to increase when the sea level is higher, which is bound to aggravate the tidal flooding hazard. In contrast, the central part of the delta will potentially experience massive flooding of river banks and adjoining lands in the scenarios exceeding 0.5 m of sea level rise. Consequently, this flooding induces a decay of the tidal amplitude in the central part. Our study shows that the tidal modulation is a significant ingredient that needs to be accounted for in the evolution of the future hydrodynamics of the Bengal delta. The friction-dominated and regionally contrasting damping and amplification mechanism also underscores the potential application of managed realignment strategy for a sustainable delta management in the future. Highlights: Robust estimate of change in tidal properties over the last decades. Comprehensive, high-resolution tidal model for the head Bay of Bengal including the Ganges-Brahmaputra-Meghna delta. Regionally-dependent, high-magnitude response of tidal properties to increasing sea level in future scenarios. Friction is the dominant mechanism of the changing tide with sea level rise. Large tidal amplification foreseen along the major embanked estuaries.